Antisickling activity of the fresh and dried roots of cissus populnea guill. Et perr (vitaceae) (2015)
Research into plants with claimed traditional use in the management of sickle cell anaemia constitutes a useful research strategy in the search for new antisickling drugs and templates. The root of Cissus populnea has been used traditionally in the management of sickle cell disease (SCD). Phytochemical screening of the fresh and powdered sample of the root of C. populnea (CP) was done using standard methods followed by in vitro antisickling evaluation of extracts, solvent-partitioned fraction (ethylacetate) and the vacuum liquid chromatographic fractions (VLC) of the fresh and dried roots of C. populnea with sodium metabisulphite induced sickling of HbSS erythrocytes. p-hydroxybenzoic acid and normal saline were used as positive and negative controls respectively. Phytochemical screening revealed the presence of tannins, saponins and cardiac glycosides. The result of this study showed that the extracts and solvent-partitioned fraction (ethylacetate) from the root of CP have antisickling property with a higher activity for the ethylacetate partitioned fraction of the dried roots compared to that of the fresh roots. The VLC fractions exhibited higher activity than the crude extracts; fraction 3 (FR3) had the maximum activity of 96.4% while 88.6% activity was demonstrated for the standard drug (PABA) at an incubation time of 45 min. This study has thus provided scientific evidence for the traditional use of CP in the management of SCD.